2018
DOI: 10.1080/00223891.2018.1449116
|View full text |Cite
|
Sign up to set email alerts
|

Selecting the “Best” Factor Structure and Moving Measurement Validation Forward: An Illustration

Abstract: Despite the broad literature base on factor analysis best practices, research seeking to evaluate a measure's psychometric properties frequently fails to consider or follow these recommendations. This leads to incorrect factor structures, numerous and often overly complex competing factor models and, perhaps most harmful, biased model results. Our goal is to demonstrate a practical and actionable process for factor analysis through (a) an overview of six statistical and psychometric issues and approaches to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
116
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(132 citation statements)
references
References 101 publications
9
116
0
2
Order By: Relevance
“…The flexibility of the potential factor solutions is maximized by using narcissism items rather than scales, subscales, or parcels. Furthermore, by utilizing an inclusive pool of over 200 items, the likely number of indicators for each factor is increased along with factor stability (Marsh et al, ; Schmitt, Sass, Chappelle, & Thompson, ). The first factor is expected to be indicative of what is most common to the narcissism scales, a grandiose sense of self‐importance.…”
Section: The “Bass‐ackward” Approach To Understanding the Narcissism mentioning
confidence: 99%
“…The flexibility of the potential factor solutions is maximized by using narcissism items rather than scales, subscales, or parcels. Furthermore, by utilizing an inclusive pool of over 200 items, the likely number of indicators for each factor is increased along with factor stability (Marsh et al, ; Schmitt, Sass, Chappelle, & Thompson, ). The first factor is expected to be indicative of what is most common to the narcissism scales, a grandiose sense of self‐importance.…”
Section: The “Bass‐ackward” Approach To Understanding the Narcissism mentioning
confidence: 99%
“…Because EC facets are positively related to each other [28], they will be hierarchically structured. Clarification of the higher-order structure of individual differences is important because it can provide a parsimonious summary of the vast complexity of human nature [38]. Given that the above 10 core EC facets are categorized into a 2 (type of target) × 5 (type of competence) framework, we can assume six possible structures.…”
Section: Introductionmentioning
confidence: 99%
“…To evaluate the best factor structure, we followed the flowchart recently proposed by Schmitt, Sass [38]. They encourage researchers to start by conducting dimensionality analyses (e.g., parallel analysis, minimum average partial test, exploratory graph analysis); then, if theoretical candidate factor structures exist, they recommend confirmatory factor analysis (CFA).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Kaiser-Meyer-Olkin measure of sampling adequacy, which was .99, and Bartlett's test of sphericity, which was significant, χ 2 (1770) = 37839.86, p < .001, provided a strong evidence for the suitability of the data for EFA (Beavers et al, 2013). To determine how many factors to retain, we first performed a parallel analysis (Hayton, Allen, & Scarpello, 2004;Horn, 1965;Schmitt, Sass, Chappelle, & Thompson, 2018), which showed that five factors should be retained. We therefore performed a maximum likelihood (ML) EFA (Table 1) with five factors and used an oblique rotation-promax-given that we expected the factors to be correlated because they belong to the same theoretical construct and because this rotation typically produces a clean factor structure (Hendrickson & White, 1964;Schmitt & Sass, 2011).…”
Section: Exploratory Factor Analysismentioning
confidence: 99%